Antimicrobial activity of compounds from Acanthospermumhispidum DC and Caesalpiniabonduc (L.) ROXB: Beninese plants used by healers against HIV-associated microbial infections - FAGLA MEDEGAN GOUSSANOU, Sèdami R. (My University, 2015)
In this study, we have tested alcoholic extracts (60%) from four Beninese plants: Ocimum gratissimum L., Acanthospermum hispidum DC, Caesalpinia bonduc (L) Roxb and Calotropis procera W. T. Aiton. They are used by the healers to prevent opportunistic diseases associated to HIV-AIDS; on six strains such as: Escherichia coli O 157H7, Staphylococcus aureus ATCC 25923 which resist to methicillin (MRSA), Salmonella typhi, Klebsiella pneumonia, Candida albicans ATCC 10231, and Mycobacterium bovis BCG 040812 which cause microbial infections associated with HIV-AIDS. The results show that all the extracts are bacteriostatic and fungistatic but only the hydro-ethanolic extracts of Acanthospermum hispidum (HE2) and of Caesalpinia bonduc (HE3) presented antibiotic power (respectively ap = 2 and ap = 4) on Candida albicans ATCC 10231. The Mycobacterium bovis BCG shown resistance to tested extracts (CMI > 250 μg/mL). The two fungicidal extracts HE2 and HE3 did not show harmful effects on the cells WI–38 with an IC50 > 100 μg/mL for HE2 and IC50 = 50 μg/mL for HE3. The successive bio-guided purifications of extracts HE2 and HE3 permitted isolation of three antibacterial compounds: Flavanone (M1); stigmasterol (M2); and quercetin (M3). The three isolated compounds possess antibiotic power (ap 3±1) on tested strains and are not toxic on shrimp larvae (LC50: 0.30 ± 0.17 mg/mL).
Keywords: Microbial infections; HIVAIDS; Beninese plants; cytotoxic activity; antimicrobial activity; chromatographic methods.